Avaliação metabólica de cavalos crioulos submetidos a provas funcionais. - Amaral, Lorena Alvariza (2012)
The Crioulos breeding horses of Brazil has been growing in recent years, however there is still a dearth of information about this breed. To characterize the physical conditioning of Crioulo horses in training for the Freio de Ouro , as well as the metabolic response of Crioulo horses subjected to Marcha de Resistencia . We written The first study aimed to determine the anaerobic threshold or limiar (V4) of Crioulo horses during training, for this 22 healthy horses were evaluated. The selected animals were submitted to a performance test on track. It consisted of three stages with increasing speed of 6m/s, 8m/s and 10m/s with five minutes duration for each step, until blood lactate concentration reached 4mmol/dL. Blood lactate concentrations increased from the exercise speed of 6,0 m/s and 90% (n=20) of the animals reached 4mmol/dL of lactate at 6-8 m/s with an average heart rate ranging from 121 to 140 bpm. Our results demonstrate that the V4 of Crioulo horse is between the speeds of 6 - 8m/s and heart rate between 121 and 140bpm.The second study aimed to characterize the metabolic responses occurring during the Marcha de Resistencia in which are traversed or running 750km in 15 days of competition. We evaluated 11 Crioulo horses, two males and nine females . Blood samples were performed 24 hours before the test and at 4, 9, 11, 14 and 15 days of competition. Were evaluated CK, AST, LDH, glucose, lactate, urea, creatinine, sodium, potassium, chloride, magnesium, total calcium, ionized calcium, total protein, hematocrit and leukocyte count. At the end of the competition mean values of serum AST were 1151 ± 358 IU/ L,the mean LDH values were 7418 ± 1695 IU/L and CK was 13,867 ± 3998UI /L. There was significant increase in urea, creatinine and lactate (p <0.0001).Was observed decrease in the mean values of chloride, sodium, potassium, total and ionized calcium (p ≤ 0.0002). The evaluation of the hematologic values found indicate increased total leukocytes and segmented (p ≤ 0.0002) and decreased values of hematocrit, plasma protein and total lymphocytes (p ≤0.0003). The values of glucose, on average remained constant. Based on these data we conclude that the competition "Marcha de Resistencia" determined high muscular demand, energy and electrolyte depletion, and suggests an inflammatory process in the animals evaluated.